Tarantism: The Italian Pizzica from Music Therapy to New Formsof Performance - Daniele Zappatore (IJCAS (International Journal of Creative and Arts Studies), 2017)
Far from being a mere historical reconstruction of the complex and culturally conditioned zymology of tarantism, the aim of this paper is to highlight its dynamic diachronically. Originally came from Italy, tarantism and its dynamics couldn’t be disjoined from its ancient concepts: cults, ritual possession, choral-music exorcism, that can be understood as a music therapy. In ethnomusicology standpoints, the particular significance would join the analysis of its from and its cultural aspect to elaborate the preservation of its choral nature or even its original ritual use in some maintained tarantellas. Through a cultural approach, this paper showed how, in the next period, political and economic development of these processes of capitalization resulting form of commodification focused in the aspects of dance and music. This lead to a decontextualization of the tarantula’s symbol into ideological discourse that transformed into cultural heritage in order to give it the status of capital goods, to be launched in cultural market.